Clinical and Dermoscopic Features of Erythema Dyschromicum Perstans: A Case Series - Kaya, Gökhan (The European Research Journal, 2026)
Objective: Erythema dyschromicum perstans (EDP) is a rare acquired dermal melanosis that clinically overlaps with lichen planus pigmentosus and Riehl’s melanosis. Its diagnosis relies on integrating clinical, dermoscopic, and histopathological features. To characterize the clinical, dermoscopic, and histopathological spectrum of EDP in a 14-patient case series and to highlight the diagnostic contribution of dermoscopy. Methods: A retrospective review was conducted of 14 biopsy-proven EDP patients diagnosed between 2023 and 2025 at a secondary care dermatology center. Demographic data, clinical distribution, dermoscopic findings, histopathology, and treatments were systematically analyzed. Results: Patients had a mean age of 41.4 years (range 21–69); 12 were female and 2 male, with Fitzpatrick skin types III–IV. Mean disease duration was 2.4 years (range 4 months–10 years). Lesions most often involved the trunk (71.4%), with additional sites including the face, upper arms, axillae, inframammary folds, and neck. Most patients were asymptomatic; two reported mild pruritus. Dermoscopy, available in ten cases, revealed a bluish-gray granular background in 90%, darker blotches in 40%, faint blurred vascular structures in 40%, and perifollicular accentuation in 20%; a diffuse cloud-like pattern was noted in one case. Histopathology consistently showed basal vacuolar alteration, pigment incontinence, and dermal melanophages, with Fontana–Masson confirming dermal melanin in selected specimens. Treatments included isotretinoin in four patients, dapsone in three, topical agents in four, while three remained untreated due to loss to follow-up. Conclusion: This series documents both sexes and rarely reported sites of EDP, including a pregnancy-associated case, and highlights reproducible dermoscopic clues that support histopathologic confirmation and aid in distinguishing EDP from other acquired dermal melanoses. Larger prospective multicenter studies are warranted to clarify therapeutic approaches and long-term outcomes.